BUDGETING AND CONTROL OF MACHINERY. - Drucker, A. P. R. (The Accounting Review, 1931)
Abstract To budget machinery raises many difficult problems. The first problem is to determine the period which the budget should cover. In budgeting the sales and production of a business, the fiscal period, usually a year, is the basis followed. A monthly detailed budget supplements the annual budget. There are several reasons for using the year as the basis for budgeting sales. First, it is the period covered by the profit and loss statement. Second, the year is a comprehensive enough period to include all the seasonal changes, and thus the relation between seasons may be determined. Third, the yearly budget provides a basis by which comparisons of similar periods in different years, or full years may be fairly made. These reason also hold good for the budgeting of production on a yearly basis, productivity depending on the same seasons fluctuation as do sales. In budgeting machinery, however, the fiscal year may not be the logical period. There is no relation between the fiscal year and machinery production.